Momentum feedback from marginally resolved H ii regions in isolated disc galaxies - Jeffreson, Sarah; Krumholz, Mark R; Fujimoto, Yusuke; Armillotta, Lucia; Keller, Benjamin W.; Chevance, Mélanie; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2021)
We present a novel, physically motivated sub-grid model for H ii region feedback within the moving mesh code arepo, accounting for both the radiation pressure-driven and thermal expansion of the ionized gas surrounding young stellar clusters. We apply this framework to isolated disc galaxy simulations with mass resolutions between 103 and 105 M⊙ per gas cell. Each simulation accounts for the self-gravity of the gas, the momentum and thermal energy from supernovae, the injection of mass by stellar winds, and the non-equilibrium chemistry of hydrogen, carbon, and oxygen. We reduce the resolution dependence of our model by grouping those H ii regions with overlapping ionization front radii. The Strömgren radii of the grouped H ii regions are at best marginally resolved, so that the injection of purely thermal energy within these radii has no effect on the interstellar medium. By contrast, the injection of momentum increases the fraction of cold and molecular gas by more than 50 per cent at mass resolutions of 103 M⊙, and decreases its turbulent velocity dispersion by ∼10 km s−1. The mass-loading of galactic outflows is decreased by an order of magnitude. The characteristic lifetime of the least-massive molecular clouds (⁠M/M⊙≲5.6×104⁠) is reduced from ∼18 to ≲10 Myr, indicating that H ii region feedback is effective in destroying these clouds. Conversely, the lifetimes of intermediate-mass clouds (⁠5.6×104≲M/M⊙≲5×105⁠) are elongated by ∼7 Myr, likely due to a reduction in supernova clustering. The derived cloud lifetimes span the range from 10 to 40 Myr, in agreement with observations. All results are independent of whether the momentum is injected from a ‘spherical’ or a ‘blister-type’ H ii region.